Design of Wideband Bandpass Filter With Simultaneous Bandwidth and Notch Tuning Based on Dual Cross-Shaped Resonator - Cheng Teng (IEEE, 2020)
In this paper, a wideband bandpass filter (BPF) with simultaneous bandwidth and notch tuning is proposed, by using a dual cross-shaped resonator (DCSR) with parallel-coupled three-line (PCTL) feeding. It is found that three intrinsic transmission zeros can be generated by the proposed DCSR, while two of the zeros are used for the implementation of passband edge zeros and the other one is for a notch. Three varactors are used to implement the bandwidth and notch tuning independently. These innovative integrated functions of both tunable bandwidth and notch in a single architecture are proposed for the first time. On the other hand, the PCTL can provide sufficiently strong coupling in the desired passband. The proposed BPF can achieve the bandwidth tuning with a fixed notch inside/outside the passband, and the bandwidth can also be kept unchanged when tuning a notch within the passband. The prototyped BPF centered at 6 GHz reports that the absolute bandwidth (ABW) can be varied from 2.5 to 5.8 GHz, while the fractional bandwidth (FBW) is tuned from 41.7% to 96.7% together with notch frequency tuning of 5.0 to 8.2 GHz. The experimental measurements are in good agreement with the theoretical analysis.